A cunha do ciclo de fácies do Grupo Guatá (Eopermiano) na margem sub-aflorante do norte paranaense - Cortez, Kátia Denise José [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
A wedge facies cycle it‟s a body of sedimentary rock, bounded above and below by unconformity and which represents a transgressive-regressive cycle of deposition. This cycle is formed by the following succession of facies: non-marine (N), transitional-coarse texture, and marine-fine texture; The objective of this study have been members of the sandstones and Triumph Siderópolis, seconded by rare calcareous sandstones and very thin limb Paraguaçu. Through analysis of facies in wells testified by CPRM, it was possible to group on facies successions and set the standard stacking. The Triunfo Member consists of three cycles of facies, lithology whose standard indicates a vertical arrangement ''type'' tuning up, other words, a component sandy bottom in the form of '' box'', followed by components sandy-clayey and clayey-carbonaceous (1st and 2nd cycle) and / or shale and limestone (3rd cycle), represented by the base member Paraguaçu. The first cycle only occurs on NF-5 wells and NF-6 in the form of Onlap channel dug in post-Itararé group. The cycle II also reaches wells NF-4 and NF-3 to the north, while the cycle III reaches the southern area, well NF-9. The member Paraguaçu, well PP-25 is predominantly clay-síltico, also stand out limestones and sandstones. The limestones are not coastal marine organisms probably connected with the algae and cyanobacteria, the sandstones are fine-textured, very thin and coastal deposition environment. The member Siderópolis, well NF-2 consists of a sandstone fluvial-estuarine deployed in the valley section, and succeeded by sandstones and siltstones bioturbed, they have linked the transgression of the Fm. Palermo

Uma cunha de ciclo de fácies é um corpo de rocha sedimentar, limitado acima e abaixo por discordâncias, e que representa um ciclo transgressivo-regressivo de deposição. Tal ciclo é formado pela seguinte sucessão de “fácies”: não-marinha (N), transicional-de textura grossa , e marinha-de textura fina; O objetivo desta pesquisa foram os arenitos dos membros Triunfo e Siderópolis, secundados por raros calcários e arenitos muito finos do membro Paraguaçu. Através de analises faciológicas em poços testemunhados da CPRM, foi possivel fazer um agrupamento em sucessões de fácies e definir o padrão de empilhamento. O Membro Triunfo é constituído de três ciclos de fácies, cujo padrão litológico indica um arranjo vertical tipo „‟afinando‟‟ para cima, ou seja, um componente arenoso inferior em forma de „‟caixa‟‟, sucedido por componentes areno-argiloso e argiloso- carbonoso (1º e 2º ciclos) e /ou folhelho e calcário (3º ciclo), representado pela base do membro Paraguaçu. O ciclo I só ocorre nos poços NF-5 e NF-6, sob a forma de onlap em canal escavado pós-grupo Itararé. O ciclo II alcança também os poços NF-4 e NF-3 ao norte, enquanto o ciclo III alcança a área sul, poço NF-9. O membro Paraguaçu, poço PP-25 é dominantemente síltico-argiloso, destacam-se também calcários e arenitos. Os calcários são costeiros a não marinhos, com organismos provavelmente ligados a algas e cianobactérias; os arenitos são de textura fina- muito fina e de ambiente costeiro. O membro Siderópolis, poço NF-2 é constituído de um arenito fluvio-estuarino implantado em vale inciso, e sucedido por arenitos e siltitos bioturbados, estes já ligados a transgressão da Fm. Palermo
Keywords: Arenito; Geologia estratigráfica; Facies (Geologia); Correlação estratigráfica; Parana, Rio, Bacia; Sandstone; Stratigraphic correlation; Geology, Stratigraphic